Development of Drill Smash Training Models in Straight and Cross Directions to Improve Volleyball Smash Results at the SONS Club (Sriwijaya State Sports School) Palembang - Krisimon, Yosua; Rahman, Andi; Putri, Siti Ayu Risma (PPSDP International Journal of Education, 2024)
This research aims to develop an effective drill training model to improve smash shot ability in two main directions, namely the straight direction and the cross direction, in volleyball. This training model is designed by taking into account the basic principles of smash technique, body regulation, strength and speed, as well as consistency in training. This research and development procedure uses the Borg & Gall steps. The research design for the development of the Borg & Gall development model is then changed to be simpler and also according to the needs of researchers which involves seven main steps: 1) Preliminary study, 2) Planning 3) Initial draft design , 4) Validation of initial drafts and revisions, 5) Small scale 6) Final product, 7) Effectiveness Test. Small scale trials were carried out at Dehasen Bengkulu University Extracurricular with a sample of 10 people and large scale trials were carried out at the Savvana Volleyball Club with a sample size of 15 people. The effectiveness test was carried out by the two clubs, each taking 10 samples to make 20 samples and testing them through prerequisite tests, namely 1) normality test, 2) homogeneity test 3) sample t test. The results of the research are that the final product is produced in the form of a model for the development of drill smash training in straight and cross directions with Root obstacle media to increase the accuracy of smashes in volleyball athletes. Very feasible” which was analyzed through the Aiken V test, with a material expert score of 0.81, media expert 0.96, small scale trial 0.90 and large scale trial 0.93 with an average criteria value of “Very High”.